Natural gas in nontechnical language - Institute of Gas Technology (Tulsa Pennwell, 1999)
Provides a balanced non-technical overview of the natural gas process from wellhead to burntip and exploration to end usage, while briefly addressing future trends, resources, and supply and demand. Text is based on educational material from the Institute of Gas Technology. DLC: Natural gas.
Includes bibliographical references and index.
Keywords: Natural gas